2017
DOI: 10.1519/jsc.0000000000001782
|View full text |Cite
|
Sign up to set email alerts
|

Ratings of Perceived Exertion During Acute Resistance Exercise Performed at Imposed and Self-Selected Loads in Recreationally Trained Women

Abstract: Cotter, JA, Garver, MJ, Dinyer, TK, Fairman, CM, and Focht, BC. Ratings of perceived exertion during acute resistance exercise performed at imposed and self-selected loads in recreationally trained women. J Strength Cond Res 31(8): 2313-2318, 2017-Resistance exercise (RE) is commonly used to elicit skeletal muscle adaptation. Relative intensity of a training load links closely with the outcomes of regular RE. This study examined the rating of perceived exertion (RPE) responses to acute bouts of RE using impose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…In studies with resistance-trained people (at least 12 months of experience with weight training), the self-selected loads were lower than those recommended for eliciting strength gains. [17,20] These studies consisted of only 1 experimental session. In the study of Faries and Lutz [28] that lasted 6 weeks, the authors observed that in the fifth training session, the loads reached those recommended by the guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies with resistance-trained people (at least 12 months of experience with weight training), the self-selected loads were lower than those recommended for eliciting strength gains. [17,20] These studies consisted of only 1 experimental session. In the study of Faries and Lutz [28] that lasted 6 weeks, the authors observed that in the fifth training session, the loads reached those recommended by the guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…However, in studies conducted with recreationally trained adults (minimum of 6 months of resistance training experience), it was observed that these loads were below the recommended intensity to enhance muscle strength. [17,20]…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, RPE was shown to have significant correlation with total volume-load, but not with HRV metrics. RPE has been shown to be a strong indicator of fatigue accumulated during resistance training programs [25,26,27,28,29,30]. The combination of subjective measures from RPE and objective measures from HRV metrics may be a viable option for measuring fatigue accumulation and tracking recovery for researchers and practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Ratings of Perceived Exertion (RPE) using the Borg CR-10 scale was collected after each training session as a means of measuring intensity and a subjective measure of fatigue accumulation. RPE was used in addition to 1RM percentage loading zones to determine intensities of the prescribed training sessions, as well as the athlete’s perception of performance [24,25,26,27]. Intra-set rest periods were 60–90 s for the first mesocycle, two minutes for the second mesocycle, two to three minutes for the third mesocycle, and three minutes for the fourth mesocycle.…”
Section: Methodsmentioning
confidence: 99%
“…Other researches show necessity of ensuring level of athletes' health: determination of correlation features of subjective and physiological parameters on reaction to load [18][19][20]; due to use of modern techniques of a cardio-strength training [21,22]; application of tests for evaluation of functionality [23][24][25]; application of biochemical tests for determination of health level [26][27][28]; increase in indicators of life quality [29][30][31].…”
Section: Pedagogics Psychologymentioning
confidence: 99%